Bankruptcy of Husband Over Joint Property (Case Study of Decision Number 165/PDT.SUS.PKPU/2018/PN.NIAGA.JKT.PST) - Pratiwi, Salma Rahmi; Sri Darmadi, Nanang (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2024)
The research aims to analyze the legal implications of husband's bankruptcy on rights and obligations regarding joint property in terms of Decision Number 165/Pdt.Sus.PKPU/2018/PN.Niaga.Jkt.Pst. The research method used is normative legal research with statutory and case approaches. The results indicate that by the implementation of the unity of property, bankruptcy experienced by the husband is treated as bankruptcy of joint property. The legal implications of the husband's bankruptcy on the rights and obligations regarding joint property that are reviewed from Decision Number 165/Pdt.Sus.PKPU/2018/PN.Niaga.Jkt.Pst, the husband and wife, Ikhwan Andi Mansyur and Ir. Indah Sari, lost their right to manage and control the assets including revocation of Personal Guarantees, because those are part of bankruptcy assets.